Validation of the Lithuanian Version of the Parental Burnout Assessment (PBA-LT) - Bredelytė, Aelita; Kreivinienė, Brigita; Skarbalius, Egidijus (Social Welfare: Interdisciplinary Approach, 2025)
Background. Parenting is both a complex and stressful activity. When parenting stress severely and chronically overwhelms parents’ resources to cope, parental burnout occurs. The purpose of this study was to validate the Parental Burnout Assessment (PBA) for researching a Lithuanian sample of parents. Methods. Questionnaire included demographics, Parental Burnout Assessment, Emotional Regulation Questionnaire, and Co-parental Cooperation tool. The data were collected from a sample of 208 Lithuanian parents. Results. The value for Cronbach’s alpha in Lithuania was high and similar to other studies. Confirmatory factorial analysis confirmed the four-factor structure of the PBA. The average parental burnout reported was higher than in other studies. The correlations of the PBA-LT with other variables replicate previous studies and serve as evidence for the validity. Younger age, having a child aged 0–4 years, not having a paid professional activity, suppression of emotions, and not having emotion regulation skills are the risk factors of parental burnout. Conclusions. The study supports the high internal consistency of PBA-LT, and the four-factor structure of the PBA-LT has been confirmed.